How can clinicians detect and treat autism early?: Methodological trends of technology use in research - Bölte, Sven (Acta paediatrica, 2016)
We reviewed original research papers that used quantifiable technology to detect early autism spectrum disorder (ASD) and identified 376 studies from 34 countries from 1965 to 2013. Publications have increased significantly since 2000, with most coming from the USA. Electroencephalogram, magnetic resonance imaging and eye tracking were the most frequently used technologies. Conclusion The use of quantifiable technology to detect early ASD has increased in recent decades, but has had limited impact on early detection and treatment. Further scientific developments are anticipated, and we hope that they will increasingly be used in clinical practice for early ASD screening, diagnosis and intervention.
Gesehen am 22.10.2019
First published: 19 October 2015